Implementasi User Autentikasi Berbasis SMS Gateway di SMK Al-Farisi Kecamatan Leles - Syani, Mamay; Tresnawati, Shandy; Rohmayani, Dini; Junia Rizqi, Kevin (POLITEKNIK NEGERI JAKARTA, 2021)
SMK Al-Farisi Leles currently provides hotspot services which is an area where there is a wireless internet connection that can be accessed through Laptops, Gadgets, and other devices that support the technology. With hotspots in SMK Al-Farisi Leles, users can enjoy internet access in the hotspot area without having to connect by cable. Hotspots in SMK Al-Farisi can be accessed directly by anyone because the authentication system is still conventional which is authentication that enters a password to be connected to the hotspot network, this often results in an unstable connection because there is no limit to being connected to the hotspot network so that people outside the school community who are in the hotspot area can also be connected freely. Therefore, the author implements SMS Gateway-based Authentication User in SMK Al-Farisi where the user is required to request first to obtain a hotspot account via SMS with the provision stipulated by the admin. The results showed that this authentication system runs smoothly and can manage users connected to hotspot networks.